Tooth size discrepancies in female patients with palatally impacted canines - Al-Nimri Kazem; Adwan Imad; Gharaibeh Tareq; Hazza'a Abdalla M. (Sciendo, 2023)
Small upper lateral incisors in patients with palatally impacted canines may contribute to inter-arch tooth size discrepancies.